Albumin and interferon-β fusion protein serves as an effective vaccine adjuvant to enhance antigen-specific CD8+ T cell-mediated antitumor immunity. Issue 4 (22nd April 2022) - Tseng, Ssu-Hsueh; Cheng, Max A; Farmer, Emily; Ferrall, Louise; Kung, Yu Jui; Lam, Brandon; Lim, Ling; Wu, T-C; Hung, Chien-Fu
Abstract : Background: Type I interferons (IFN) promote dendritic cells maturation and subsequently enhance generation of antigen-specific CD8 +T cell for the control of tumor. Using type I interferons as an adjuvant to vaccination could prove to be a potent strategy. However, type I interferons have a short half-life. Albumin linked to a protein will prolong the half-life of the linked protein. Methods: In this study, we explored the fusion of albumin to IFNβ (Alb-IFNβ) for its functional activity both in vitro and in vivo. We determined the half-life of Alb-IFNβ following treatment in the serum, tumor, and tumor draining lymph nodes in both wild type and FcRn knockout mice. We characterized the ability of Alb-IFNβ to enhance antigen-specific CD8+ T cells using ovalbumin (OVA) or human papillomavirus (HPV) E7 long peptides. Next, we evaluated the therapeutic antitumor effect of coadministration of AlbIFNβ with antigenic peptides against HPVE7 expressing tumor and the treatment's ability to generate HPVE7 antigen specific CD8+ T cells. The contribution of the antitumor effect by lymphocytes was also examined by an antibody depletion experiment. The ability of Alb-IFNβ to serve as an adjuvant was tested using clinical grade therapeutic protein-based HPV vaccine, TACIN. Results: Alb-IFNβ retains biological function and does not alter the biological activity of IFNβ. In addition, Alb-IFNβ extends half-life of IFNβ in serum, lymph nodes and tumor. The coadministration of Alb-IFNβ with OVA or HPVE7 antigenic peptides enhances antigen-specific CD8 +T cell immunity, and in a TC-1 tumor model results in a significant therapeutic antitumor effect. We found that CD8 +T cells and dendritic cells, but not CD4 +T cells, are important for the observed antitumor therapeutic effect mediated by Alb-IFNβ. Finally, Alb-IFNβ served as a potent adjuvant for TA-CIN for the treatment of HPV antigen expressing tumors. Conclusions: Overall, Alb-IFNβ serves as a potent adjuvant for enhancement of strong antigen-specific CD8 +T cell antitumor immunity, reduction of tumor burden, and increase in overall survival. Alb-IFNβ potentially can serve as an innovative adjuvant for the development of vaccines for the control of infectious disease and cancer.